Effects of intercropping sunn hemp into maize at different times and densities on productivity under rainwater harvesting technique - Dzvene, Admire R.; Tesfuhuney, Weldermichael; Walker, Sue; Ceronio, Gert (Frontiers in Sustainable Food Systems, 2022)
Maize is a major food crop in Sub-Saharan Africa (SSA), and its productivity is affected by climate change-adaptive sustainable management practices. A 2-year field study (2019/20 and 2020/21 growing seasons) was carried out to evaluate the effect of sunn hemp (Crotalaria juncea L.) living mulch management on maize (Zea mays L.) production. Three sunn hemp planting periods were simultaneous with maize planting (P1), V15 maize growth stage (P2), and R1 maize growth stage (P3) and three densities 16.1 plants m−2 (D1-low), 32.1 plants m−2 (D2-medium), and 48.1 plants m−2 (D3-high). The intercrop components were planted in a split-plot treatment arrangement as an additive series with three replications and laid out in a randomized complete block design under the in-field rainwater harvesting (IRWH) technique. The growing season conditions revealed significant differences in rainfall distribution. Therefore, the planting period had highly significant (p < 0.001) effects on sunn hemp biomass, with an LSD value of 610.2 kg ha−1, showing that the highest was obtained in P2 (2636.7 kg ha−1) compared to P3 (811.3 kg ha−1). However, the P3 treatment resulted in maize grain yield penalty, with yields as follows: P3 (2775.2 kg ha−1), sole maize (3263.8 kg ha−1), P2 (3281.9 kg ha−1), and P1 (3287.8 kg ha−1). P2 yielded a significantly (p < 0.05) high-income equivalent ratio of 2.09, indicating a 109% advantage for increasing farmers' income by integrating sunn hemp under the no-till area of IRWH. P1 and P2 sunn hemp planting periods are viable options for smallholder farmers in summer rainfall regions to improve economic benefits.